(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Thyroid gland is the most important gland of the endocrine system. Thyroid hormones manage the metabolic activity of the body. When the secretion of these hormones gets hampered, the thyroid gland fails to complete the metabolic need of the body. This condition is called as hypothyroidism. This problem is a great challenge for both developing as well as developed countries. It is seen 7 to 8 times more common in females than males. The only treatment available is levo-thyroxine tablets which patients have to take lifelong. Due to high prevalence of the disease in the society, the present study was taken to evaluate the efficacy of the management by Ayurvedic principles. In Ayurvedic literature there is no direct reference of this disease. It may be considered due to the disfunctioning of Jatharagni which may leads to the manifestation of this disease. According to the symptoms of this disease, dominance of Dosha may be understand as Pittaand Kapha. Virechana is the best treatment for the Pitta Dusthi and also an effective treatment for the Kapha Dosha. Hence, in present study, total 20 patients of hypothyroidism with TSH more than 5.0 mIU/ml irrespective of the level of serum T3 and T4 were selected and treated with Virechana karma with Araghvadhadi yoga. Effect of Virechana karma was seen extremely significant on symptoms like fatigue, dry and coarse skin, unexplained weight gain, muscle ache, puffiness of face and breathlessness. After the treatment, the average TSH value reduced from 153.03 to 138.41. This is observed that the TSH level was reduced up to 9.88%.